Генеральна військова музика XVII–XVIII ст.: історія, структура та функційне призначення - Горенко, Л.І. (Сіверщина в історії України, 2014)
У статті висвітлено роль гетьмансько-старшинської верстви у формуванні та розвитку культурно-музичного життя в
Україні другої половини XVII–XVIII ст. Розглянуто діяльність
представників цієї верстви у царині музичної освіти та культури в
Україні, особливості її музичного побуту та культурно-мистецьких
зв’язків в Україні та за її межами. До репрезентативної сфери
суспільно-політичного та культурно-музичного життя козацько-
гетьманської держави також належала діяльність військових
музикантів і, насамперед, генеральної військової музики. Гетьмани
та старшина виступили охоронцями національної музичної
культури, здійснили визначний вплив на її подальший розвиток. В статье отображена роль гетманско-старшинской
среды в формировании и развитии культурно-музыкальной
жизни в Украине второй половины XVII–XVIII ст. Раскрыта
деятельность представителей этого сословия в сфере
музыкального образования и культуры в Украине, особенностей
их музыкального быта и культурно-художественных связей в
Украине и зарубежом. К репрезентативной сфере общественно-
политической и культурно-музыкальной жизни казацко-
гетманского государства также принадлежит деятельность
военных музыкантов и, прежде всего, генеральной военной музыки. Гетманы и старшина выступили охранниками
национальной музыкальной культуры, совершили значительное влияние на её дальнейшее развитие. In the thesis the author researches the role of Hetman’s
stratum in the creation and development of the music-cultural life
in Ukraine in the second half of the XVII–XVIII-th century. The
autor examines the Hetman’s stratum representatives activity in the
sphere of music education and culture in Ukraine, the particularities
of their musical mode and music-cultural relations inside and
outside Ukraine. The autor comes to a conclusion, that suitable
conditions for the development of national culture, the formation of
high music education and art playing in Ukraine were made under
the support of Hetman’s government in the middle of the XVIIIth
century. The estates of the representatives of Hetman’s stratum
became the national culture centers, where diferent forms of secular
music art were being created and professional music specialists
being educated. The military musician activity belonged to the
representative shpere of social, political and music-cultural life of
the Hetman-Cossacks’ state. Hetman and high ranks of Cossack
forces became the defenders of national culture, made a great
influence on its future development.